2003
DOI: 10.1046/j.1525-1594.2003.07159.x
|View full text |Cite
|
Sign up to set email alerts
|

Intraportal Transplantation of Allogenic Pancreatic Islets Encapsulated in Barium Alginate Beads in Diabetic Rats

Abstract: The survival of microencapsulated islets transplanted into the unmodified peritoneal cavity is limited, even if capsular overgrowth is restricted to a minimum, due to an insufficient oxygen supply to the islets. Therefore, research efforts should focus on finding or creating a transplantation site, which permits a closer contact between the encapsulated islets and the blood. For this reason, the liver could be an interesting candidate. The aim of the present study was to test the hypothesis that the intraporta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 11 publications
0
25
0
Order By: Relevance
“…Nonencapsulated islets may be injected into the liver (4,16,18,19,35,44,50,52) , kidney (5,14,15,16,17,24,27,28,32,34,35,42,46,47) , peritoneal cavity (11,35) , bone marrow (41) and subcutaneous tissue (22,48) . Ikebukuro et al (19) showed that islets and bone marrow cells, when injected into the liver using irradiation as immunosuppression, can increase the functionality of the cells for more than 365 days.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonencapsulated islets may be injected into the liver (4,16,18,19,35,44,50,52) , kidney (5,14,15,16,17,24,27,28,32,34,35,42,46,47) , peritoneal cavity (11,35) , bone marrow (41) and subcutaneous tissue (22,48) . Ikebukuro et al (19) showed that islets and bone marrow cells, when injected into the liver using irradiation as immunosuppression, can increase the functionality of the cells for more than 365 days.…”
Section: Discussionmentioning
confidence: 99%
“…> 365 Spadella et al (50) 1500 365 Schneider et al (44) 1500 97 ± 2 Omer et al (35) 4000 70 Taira M. et al (52) 600 30 Ikebukuro et al (18) 600 250…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the infusion of islets with some other pancreatic tissues 23 February 15, 2012|Volume 3|Issue 1| WJGP|www.wjgnet.com (acinar cells, ductal cells or connective tissues) in the portal vein always has a risk of causing portal hypertension and portal vein embolization [71] . Schneider et al [72] transplanted microencapsulated rat islets (with alginate) into the livers of mice, but only a 1 wk normalization in the blood glucose level was achieved. We revealed [70] that transplanted islets suffer from ischemia due to embolization by the islets themselves.…”
Section: Ideal Transplantation Site For Encapsulated Isletsmentioning
confidence: 99%
“…83 The liver has also been investigated as a possible transplant site for islet microcapsules. 84 It may be possible to transplant the islet microcapsules through an intra-portal injection, eliminating the need for surgical implantation of the encapsulated islets. 85,86 For these reasons, many researchers are investigating extra-peritoneal sites for the transplantation of islet cells.…”
Section: Transplantation Sitementioning
confidence: 99%